Plant recruitment six years after the Samarco’s tailings-dam disaster: Impacts on species richness and plant growth - André Araújo da Paz; Diego Shimizu-Aleixo; Astrid de Oliveira-Wittmann; Florian Wittmann; Cleberson Ribeiro; Ricardo Ildefonso de Campos (PLoS ONE, 2025)
One of the greatest tragedies in Brazilian mining history occurred in November 2015 in Mariana, Minas Gerais state, when a dam from the mining company Samarco was breached. Millions of mine tailings from this upstream embankment were dumped over the Doce River basin, impacting an area of approximately 1469 ha of riparian vegetation. Our objective was to experimentally investigate whether plant recruitment and establishment are impaired in areas affected by tailings six years after the deposition. To achieve this goal, in 2021 we compared soil chemical properties between affected and unaffected areas, performed a soil seed bank experiment in controlled conditions, and conducted a greenhouse growth experiment using the two most abundant plant species. Affected soils presented lower fertility and organic matter content. At the same time, the mean abundance and richness of emerging plants did not differ between soils. Still, affected areas exhibited approximately 35% lower accumulated species richness (gamma diversity) than unaffected ones. The three most abundant species in both areas represented 34% of the individuals, being Marsypianthes chamaedrys (Vahl) Kuntze, Ludwigia octovalvis (Jacq.) P.H. Raven and Ageratum conyzoides L. In the growth experiment, plants growing in affected soils presented reduced height and stem diameter increment (L. octovalvis) or allocated fewer resources to root production than aerial parts (M. chamaedrys), potentially in response to soil infertility and density. Even after six years, our results showed that tailings-affected areas continue to experience negative impacts on plant recruitment, highlighting its adverse effects on ecosystem functions and services.